Tehnologija in skrajševanje časov razvoja novih izdelkov - Pogačnik, Marjan (Strojniški vestnik, 2000)
Changes in the business environment during the last decade have significantly influenced the new product development process. As a result, the position of the technology, as a part of this process, has also been modified. The neverending conflict between design and technology functions was overcome by a new type of product development process which is based on project management principles. On this basis, powerful methods such as quality function deployment (QFD) can also be used to ensure target oriented work which will result in satisfied customers ( inside or outside of the company).The effects can be seen as an enormous reduction in new product launching times, which is particularly noticeable in the automotive industry, electronic industries and other branches where competitiveness requires fast responses to market changes.
Keywords: razvoj izdelkov; časi razvoja; skrajševanje časov; tehnologije; organizacija proizvodnje; čas; hiša kakovosti